Mixing of Genres and Aesthetic Renewal in the Poetic Art of Belkheir Okab - Houichi, abla (El Omda in Linguistics and Discourse Analysis, 2023)
The Algerian poet Belkheir Okab has demonstrated, through his modern poetic writing and from a genre-based perspective, the complexity of diversity, which has revealed a number of formal and aesthetic features. This involves a liberation from the linearity of traditional writing and the formation of a hybrid mixture aimed at aesthetic renewal and textual modernity. Okab’s poetic art is characterized by innovative and even revolutionary writing. Engaged in continuous innovation and creativity within the text, his poetry overlaps with different artistic genres and highlights the extent of poetry’s contribution to the arts. His writings embody models for the integration of poetry with other art forms, such as visual arts, theatrical arts, and narrative arts. This blending of genres and crossing of narrative codes produces a new hybrid and mixed form of writing that responds to the sensibilities of the creative artist.